ChemInform Abstract: Synthesis of Quinazolin‐4(3H)‐ones via Amidine N‐Arylation. Issue 23 (16th May 2013) - Li, Bryan; Samp, Lacey; Sagal, John; Hayward, Cheryl M.; Yang, Christine; Zhang, Zhijun
Abstract A high throughput route towards the orally active calcium‐sensing receptor antagonist (XIIIb) is developed.